Structural asymmetries and financial imbalances in the eurozone - Ivan Jaccard; Frank Smets (European Central Bank (ECB), 2017)
Almost two decades after the introduction of the common currency, differences in institutional frameworks remain a major source of cross-country heterogeneity in the eurozone. We develop a two-country model with incomplete international markets in which the availability of credit depends on the country's institutional environment. Our main finding is that structural differences in domestic credit environments provide an explanation for the procyclicality of net capital inflows observed in the South of Europe. We show that frictions in domestic credit markets generate asymmetries in the transmission mechanism of shocks that are common to both regions.
Keywords: F32; F20; G17; 330; Cross-border financial markets; eurozone crisis; incomplete international asset markets; structural reforms